Minor C-geranylated flavanones from Paulownia tomentosa fruits with MRSA antibacterial activity - Navrátilová, Alice; Schneiderová, Kristýna; Veselá, Daniela; Hanáková, Zuzana; Fontana, Anna; Dall'Acqua, Stefano; Cvačka, Josef; Innocenti, Gabbriella; Novotná, Jana; Urbanová, Marie; Pelletier, Jerry; Čížek, Alois; et al. (Phytochemistry, 2013)
Exhaustive chromatographic separation of the chloroform portion of the ethanolic extract obtained from Paulownia tomentosa (Thunb). Steud. (Paulowniaceae) fruits has led to isolation of ten C-6 geranylated flavanones tomentodiplacone C-I and mimulone C-E, featured by 3'-methoxy and 4'-hydroxy or 4'-hydroxy substitution of the B-ring of the flavonoid, respectively. The structures of these compounds were determined by using mass spectrometry (including HRMS) and 1D and 2D NMR spectroscopy. The absolute configurations of the compounds at C-2 were determined using circular dichroism. The obtained compounds showed the presence of a geranyl moiety functionalized by a carbonyl, hydroxyl or methoxyl group, or by formation of tetrahydrofuran or fused-pyrane ring, respectively. All of the flavanones described were isolated for the first time from a natural source. The antibacterial activities of selected compounds isolated along with the previously isolated geranylated flavanones were evaluated against a common panel of microbes and MRSA strains. The selected isolated compounds were tested for their ability to affect eukaryotic translation initiation via dual-luciferase reporter assay (firefly and renilla).
Keywords: iniciace translace peptidového řetězce; Fruit; reportérové geny; Methicillin-Resistant Staphylococcus aureus; Animals; Genes, Reporter; luciferasy; Flavanones; Microbial Sensitivity Tests; Magnoliopsida; Anti-Bacterial Agents; Luciferases; zvířata; ovoce; methicilin rezistentní Staphylococcus aureus; mikrobiální testy citlivosti; flavanony; antibakteriální látky; Peptide Chain Initiation, Translational